Changes in chromatin structure at recombination initiation sites during yeast meiosis. - Ohta, K (1994)
Transient double-strand breaks (DSBs) occur during Saccharomyces cerevisiae meiosis at recombination hot spots and are thought to initiate most, if not all, homologous recombination between chromosomes. To uncover the regulatory mechanisms active in DSB formation, we have monitored the change in local chromatin structure at the ARG4 and CYS3 recombination hot spots over the course of meiosis. Micrococcal nuclease (MNase) digestion of isolated meiotic chromatin followed by indirect end-labeling revealed that the DSB sites in both loci are hypersensitive to MNase and that their sensitivity increases 2- to 4-fold prior to the appearance of meiotic DSBs and recombination products. Other sensitive sites are not significantly altered. The study of hyper- and hypo-recombinogenic constructs at the ARG4 locus, also revealed that the MNase sensitivity at the DSB site correlates with both the extent of DSBs and the rate of gene conversion. These results suggest that the local chromatin structure and its modification in early meiosis play an important role in the positioning and frequency of meiotic DSBs, leading to meiotic recombination.